Evolution of oil exports and its effect on the economy of Ecuador post-COVID - María Francisca Cazorla Logroño; Emilio Fernando Santillán Villagómez; Gabriela Cecilia Quirola Quizhpi; Alba Karina Olivo Cobos (Dominio de las Ciencias, 2023)
The COVID-19 outbreak has put the Ecuadorian government under strain and made it more difficult for them to achieve its developmental goals. This review of the literature focuses on the economics, poverty, health, education, and lockdown measures while analyzing oil export in Ecuador and proving the consequences of the epidemic and lockdown measures. The time period considered to look at how COVID-19 affects estimates of oil export and its impacts on Ecuador's economic expansion. According to the economic indicator, the results indicate that the policies were ineffective at preserving exports since there was an increase in unemployment, poverty, and extreme poverty. Because of the outbreak, Ecuador's economy is now less able to expand due to recent changes. Ecuador's projected growth rate from 2015 to 2019 was one of the lowest at a pathetic 1% before the Covid-19 epidemic last year. The growth rate could have performed better due to outrageously high exchange rates and various structures and laws. When the outbreak initially began, the government lacked the assets and financial adaptability required to control a tragedy of this magnitude. In the end, an organic GDP loss of a record-low 7.8 percent occurred in 2020, raising unemployment and poverty rates. If the COVID-19 issue is to have a substantial impact and impede advancement, adjustments are required. The COVID-19 epidemic caused a drop in worldwide industrial production, which led to less oil consumption and a drop in the price of a barrel. In the past, significant drops in oil prices have frequently been correlated with depressed economies.